1995
DOI: 10.1557/jmr.1995.2042
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of structure and composition in sol-gel-derived lead zirconate titanate thin layers

Abstract: The evolution of structure and chemical distribution in sol-gel derived Pb(Zr0.53T10.47)O3 thin layers was monitored by x-ray diffraction, analytical electron microscopy, and diffuse reflectance Fourier transform infrared spectroscopy. Electron microscopy confirmed the as-deposited coatings were amorphous with short-range order. Medium-range order developed on heat treatment, and chemical heterogeneity was observed at the nanoscale. The extent of compositional heterogeneity decreased with increasing temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…[30][31][32][33] Our TEM observations agreed with these findings. The perovskite phase nucleated at the filmsubstrate interface (Fig.…”
Section: B Crystallization Of Micropatterned Linessupporting
confidence: 90%
“…[30][31][32][33] Our TEM observations agreed with these findings. The perovskite phase nucleated at the filmsubstrate interface (Fig.…”
Section: B Crystallization Of Micropatterned Linessupporting
confidence: 90%
“…During PT or lead zirconate titanate (PZT) syntheses using chemical methods, an intermediate pyrochlore or fluorite crystalline phase has been reported before the formation of the perovskite phase; identification of this phase strongly suggests phase segregation or stoichiometric deviation during synthesis. 1,2 Leite et al 3 recently showed that the polymeric precursor method is a suitable synthetic route to obtain the PT phase. These authors reported that the cubic perovskite PbTiO 3 (c-PT) phase was formed from an inorganic amorphous precursor at a temperature of 444°C.…”
Section: Introductionmentioning
confidence: 99%
“…[3] observed that one of the frequently cited advantages of sol-gel processing was the improved chemical homogeneity that might be achieved in solution. By transmission electron microscopy study, the authors demonstrated that when heated at 300°C Pb(Zr 0.53 Ti 0.47 )O 3 thin films were compositionally heterogeneous on the nanoscale, and that during heat treatment at 600°C, through diffusion processes a compositionally uniform perovskite phase resulted.…”
Section: Introductionmentioning
confidence: 99%
“…By transmission electron microscopy study, the authors demonstrated that when heated at 300°C Pb(Zr 0.53 Ti 0.47 )O 3 thin films were compositionally heterogeneous on the nanoscale, and that during heat treatment at 600°C, through diffusion processes a compositionally uniform perovskite phase resulted. Sengupta et al [4] found that Pb cations do not participate in the bonding with Ti and Zr in PbTiO 3 and PZT amorphous powder heated at 375°C and 425°C, respectively; even in the PbZrO 3 (PZ) amorphous powder (500°C) where Zr-O-Pb bonds do form, Zr-O-Zr bonds are still present. Feth et al [5] found that the local order of metal atoms in the amorphous PbTiO 3 , PZ, and PZT was completely different from that in the perovskite structure, but resembled the local order of the individual metal oxides: local environment of lead in amorphous samples corresponded to the structure of tetragonal PbO; the local structure around zirconium was similar to that in monoclinic ZrO 2 , while Ti environment corresponded to the structure of tetragonal TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation